Combined effects of CO2 and temperature on carbon uptake and partitioning by the marine diatoms Thalassiosira weissflogii and Dactyliosolen fragilissimus. (2nd March 2015) - Taucher, J.; Jones, J.; James, A.; Brzezinski, M. A.; Carlson, C. A.; Riebesell, U.; Passow, U.
Abstract Carbon uptake and partitioning of two globally abundant diatom species, Thalassiosira weissflogii and Dactyliosolen fragilissimus, was investigated in batch culture experiments under four conditions: ambient (15°C, 400 μatm), high CO2 (15°C, 1000 μatm), high temperature (20°C, 400 μatm), and combined (20°C, 1000 μatm). The experiments were run from exponential growth into the stationary phase (six days after nitrogen depletion), allowing us to track biogeochemical dynamics analogous to bloom situations in the ocean. Elevated CO2 had a fertilizing effect and enhanced uptake of dissolved inorganic carbon (DIC) by about 8% for T. weissflogii and by up to 39% for D. fragilissimus. This was also reflected in higher cell numbers, build‐up of particulate and dissolved organic matter, and transparent exopolymer particles. The CO2 effects were most prominent in the stationary phase when nitrogen was depleted and CO2(aq) concentrations were low. This indicates that diatoms in the high CO2 treatments could take up more DIC until CO2 concentrations in seawater became so low that carbon limitation occurs. These results suggest that, contrary to common assumptions, diatoms could be highly sensitive to ongoing changes in oceanic carbonate chemistry, particularly under nutrient limitation. Warming from 15 to 20 °C had a stimulating effect on one species but acted as a stressor on the other species, highlighting the importance of species‐specific physiological optima and temperature ranges in the response to ocean warming. Overall, these sensitivities to CO2 and temperature could have profound impacts on diatoms blooms and the biological pump.